Burnout in anesthesiology - Sousa,Ana Rafaela Campos (2018)
Abstract Background and objectives Burnout is a chronic condition caused by high levels of stress and anesthesiology is a stressful medical specialty with more vulnerability to burnout. The aim of this study is to review the characteristics and impact of burnout in anesthesiology. Contents In this review, the stressors and risk factors, manifestations, assessment, complications, management and prevention of burnout as well as the inconsistent research found in the state-of-art are approached. Conclusions Anesthesiologists are in a high-risk group to develop burnout, with different manifestations and consequences such as suicide or medical errors. Although there is no specific treatment yet, there are a lot of helpful measures to cope this condition. Prevention is considered an important step in order to reduce the prevalence of burnout.